Educational Introduction to ASEAN Countries for Class VIII Middle School Students Using Game Media - Muhammad Aji; Hafizh Nur Fauzi (Journal of Multimedia Trend and Technology, 2023)
Current technological developments are increasingly rapid. The use of games supports students in the learning process in class. When the material is about getting to know countries in ASEAN, students will be more likely to get bored because the introduction to maps of countries, capital cities, and natural features can only be found in books. There needs to be learning media that must be used by teachers so that students don't get bored quickly in learning. The ASEAN Country Introduction application is intended for elementary school students to study and get to know ASEAN Member Countries, where students can learn more easily than just reading about it in books, which sometimes have less interesting content, and also to increase their knowledge. This research aims to make it easier for teachers to deliver material and make it easier for students to learn material introducing ASEAN countries. This educational game was developed using the MDLC (Multimedia Development Life Cycle) method. Therefore, an educational game introducing countries in ASEAN was created which follows the "Merdeka Belajar" curriculum. From the results of the survey of 30 respondents, an average score of 92.19% was obtained so that they were included in the Strongly Agree category for games to be applied as alternative learning media.